THE EFFECTIVENESS OF PROGRAM IMPLEMENTATION IN REGIONAL REGULATIONS CONCERNING REGIONAL HEALTH INSURANCE PLUS - IVA YULIANINGSI BAHAR; MARTHEN ARIE; SABIR ALWY (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
The purpose this paper is to analyze the effectiveness of the implementation of the program in the regional regulation on regional health insurance plus in Sinjai Regency. This study uses an empirical legal research type, using a statutory approach and a conceptual approach. The data used are primary data and secondary data obtained through interviews and literature study, the data collected is then analyzed qualitatively. The results showed that the implementation of the program in the regional regulation on regional health insurance plus in Sinjai Regency was effective. In the context of implementing government affairs in the health sector in Sinjai Regency, in the context of implementing government affairs in the health sector in Sinjai Regency, statistics show that in 2021, there will be 9.77 percent of morbidity rates. Then, in terms of health care facilities, it can be seen that in 2021 in Sinjai Regency, there will be 1 hospital, 0 maternity homes, 16 community health centers with 10 ordinary categories, 5 remote categories, 1.88 very remote categories. community health assistants with the usual category of 0 mobile community health centers, 364 posyandu and 59 supporting public health center (puskesmas pembantu/pustu) and Poskesdes as many as 13. Furthermore, regarding the sociological conditions in the administration of health affairs in Sinjai Regency, related to infectious disease sufferers in 2021, it can be seen that based on the classification of the 10 most common types of disease, there were 9048 cases of hypertension, 6,509 cases of dyspepsia, 4,203 acute respiratory infection, 3599 dermatitis and eczema, 3381 cases of myalgia, 2459 cases of fever with unknown cause, and 2072 cases of cephalgia. Common cold as many as 1871 cases, caugh/cough in 1850 cases, and non-specific diabetes mellitus in 1845 cases. However, home care and home visit service programs, public safety center 119, one-stop outlets, and patient shelters have made it possible to handle it properly.